‘Kun en lidende Gud kan redde os’: Slavoj Žižek og lidelsens problem - Karlsen, Mads Peter (Dansk Teologisk Tidsskrift, 2024)
This article engages with the problem of human suffering from the philosophy of religion perspective through a presentation of Slavoj Žižek’s exposition of a number of theological key themes related to this problem. The focal point is Žižek’s claim that the crucial aspect of human suffering has to do with our attempts to ascribe a higher meaning to it. The first section of the article introduces the problem of suffering and its theological stakes through a reading of Freud and Nietzsche, who constitute an essential part of Žižek’s context. The next two sections account for Žižek’s interpretations of the Book of Job, focusing on his notion of Job as a critic of theodicy-arguments and as an anticipator of Christ. The fourth part of the article reads Žižek’s interpretation of Christ’s suffering on the cross as a critical engagement with the classical doctrines of reconciliation. The article ends with some concluding remarks.